PENGARUH PRESTASI BELAJAR SISWA TERHADAP PILIHAN KARIR SISWA KELAS XII SEKOLAH MENENGAH KEJURUAN - Fahmi Fahrul Dzikri, - (2022)
This research is motivated by the existence of qualifications in work such as the minimum value of learning achievement when choosing a job. The learning achievement is in the form of values as a measure of student success, which is indicated by the number of report cards. Good learning achievement is an expectation of every student, but seeing the reality today there are still many students who do not have good learning achievements so that students are not ready to compete in the world of work. This study aims to determine the effect of student achievement on career choices for class XII VHS students. This type of research has two variables, namely student achievement variable (X) and career choice variable (Y). The population in this study were students of class XII VHS in the Cileunyi and Jatinangor sub-districts. The sample in the study amounted to 299 class XII students who were taken by considering the rank of students in the class. Collecting data on student achievement variables and career choice variables using a questionnaire. The data analysis technique used is descriptive statistics, simple linear regression prerequisite test which includes validity test, normality test, linearity test and simple linear regression analysis with the help of SPSS 24 software. 0.734 of the output obtained a coefficient of determination (R square) of 0.539, which implies that the effect of the independent variable (student achievement) on the dependent effect (student career choice) is 53.9%.